Behavioral synergic relations between eye and postural movements in young adults searching to locate objects in room inside houses - Bonnet, Cédrick T.; Barela, Jose [UNESP]; Singh, Tarkeshwar (Springer Nature, 2022)
During precise gaze shifts, eye, head, and body movements exhibit synergic relations. In the present study, we tested the existence of behavioural synergic relations between eye and postural movements in a goal-directed, precise, visual search task (locate target objects in large images). More precisely, we tested if postural control could be adjusted specifically to facilitate precise gaze shifts. Participants also performed a free-viewing task (gaze images with no goal) and a fixation task. In both search and free-viewing tasks, young participants (n = 20; mean age = 22 years) were free to move their eyes, head, and body segments as they pleased to self-explore the images with no external perturbation. We measured eye and postural kinematic movements. The results showed significant negative correlations between eye and postural (head and upper back) movements in the precise task, but not in the free-viewing task. The negative correlations were considered to be stabilizing and synergic. Indeed, the further the eyes moved, the more postural variables were adjusted to reduce postural sway. These results suggest that postural control was adjusted to succeed in subtle and active self-induced precise gaze shifts. Furthermore, partial correlations showed significant relations between (1) task performance to find target objects and (2) synergic relations between eye and postural movements. These later results tend to show that synergic eye-postural relations were performed to improve the task performance in the precise visual task.
Keywords: Ecological scenes; Postural control; Synergy; Task performance; Visual search; Young adults